The Impact of HGU Land Conversion on Community Socio-Economy from An Islamic Economic Perspective - Adam, Muhammad; Batubara, Maryam; Bi Rahmani, Nur Ahmadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This land conversion phenomenon occurs due to competition in land use between the agricultural sector and the non-agricultural sector which arises as a result of three economic and social phenomena, namely limited resources, population increase, and economic growth. It is inevitable that as people's demand for houses increases, many plantation lands are being converted or reorganized into housing. For this research, a qualitative research method using a phenomenological approach tries to explain or reveal the meaning of concepts or experiential phenomena based on awareness that occurs in several individuals. The impact of land conversion that occurred in the village of Sampali on the social economy for residents who are descendants of PTPN 2 retirees, they lost their homes and as compensation they were given charity, and for the surrounding community, with the conversion of plantation land to housing, progress occurred in the area. This is because land clearing and the development that will be carried out can have an impact on the economy of the surrounding community. If viewed according to Islamic economics, the conversion of functions that occurs is permitted as long as the conversion of land is carried out fairly. The housing development is based on the high demand for housing in the community, so housing construction carried out by the private sector is felt to be very beneficial for the community.